Fandom and Identity Construction: An Analysis of Thai Boys Love Fandom and Fanshipping on Social Media X - Zahra, Fatma Nuraini (The Indonesian Journal of Communication Studies, 2025)
Fandom has now become a prominent popular culture phenomenon, including in Indonesia. The growing interest in Thai pop culture among younger generations has led to the emergence of various Thai fandoms, one of which is the Thai Boys Love (BL) fandom. The majority of Thai BL fans are young heterosexual women who consume homosexual narratives through Thai series. These fans, known as sao-y, engage in shipping practices by pairing two male actors featured in Thai BL dramas. This article explores the Thai BL fandom and fanshipping practices in Indonesia, as well as the identity construction of fans on the social media platform X. This study employs a qualitative descriptive approach using a case study method, with data collected through observation, interviews, and documentation. The findings reveal that fans within the Thai BL fandom on X are no longer passive audiences but active participants who reproduce media texts through fanshipping practices, demonstrated in forms of semiotic productivity, enunciative productivity, and textual productivity. In terms of identity formation, the Thai BL fandom constructs cultural identity through representational practices and meaning making performed by the fans. These activities reflect the active roles of fans on social media X in sustaining and strengthening their fandom community, while simultaneously contributing to the development of a collective identity that distinguishes Thai BL fans from other fandom groups.